The Impact of Artificial Intelligence (AI) in Teaching English in Higher Education: Challenges and Opportunities - Zainuddin; Beny Hamdani (Darussalam English Journal (DEJ), 2025)
This research investigates the influence of artificial intelligence (AI) on English language instruction in higher education, exploring both its potential benefits and challenges. A mixed-method approach was utilized, integrating survey data with in-depth interviews. The questionnaire was distributed via Google Forms through WhatsApp groups and personal networks to English lecturers. The study involved 16 English lecturers from both public and private universities in East Java. Analyzing the survey responses and interview transcripts revealed that AI technology presents both opportunities and obstacles in English language education. AI has brought significant changes to English instruction at the university level, with lecturers employing various AI tools for tasks such as generating and responding to questions, assessing grammatical accuracy, detecting plagiarism, paraphrasing, and conducting literature reviews. This research also underscores AI’s benefits in language education, particularly in grammar correction and plagiarism detection. However, alongside its advantages, AI also introduces new challenges for the future of English teaching. The effective integration of AI necessitates strong digital literacy skills. As AI technology continues to develop, there is a possibility that certain aspects of English teaching may become automated. Consequently, English lecturers need to continuously refine their digital skills to maintain their relevance in the evolving educational landscape.